Homocysteine induces DNA synthesis and proliferation of vascular smooth muscle cells by interfering with MAPK kinase pathway - KARTAL ÖZER, NESRİN (IOS PRESS, 2005)
Hyperhomocysteinemia has been identified as an important and independent risk factor for cerebral, coronary and peripheral atherosclerosis. However the mechanisms by which homocysteine promote atherosclerotic plaque formation are not clearly defined. Earlier reports have suggested that homocysteine exert its effect via the H2O2 produced during its metabolism. To evaluate which signalling molecules are involved in homocysteine induced atherosclerotic changes during the pathogenesis of vascular diseases, we examined homocysteine induced smooth muscle cell proliferation in the presence of different signal transduction inhibitors. We show that MAPK kinase pathway is involved in homocysteine induced DNA synthesis and proliferation of vascular smooth muscle cells in the presence of the peroxide scavenging enzyme, catalase. Our data suggest that homocysteine induces smooth muscle cell growth through a pathway that is independent of H2O2, that involves MAPK kinase activation, and that results in accelerated atherosclerosis.
Keywords: homocysteine; atherosclerosis; signal transduction; smooth muscle cells; ACCELERATES ATHEROSCLEROSIS; SIGNAL-TRANSDUCTION; GENERATION; ACTIVATION; INDUCTION; DISEASE; GROWTH; INJURY; RISK